Effect of Online Teaching Methods on Dental Education among Undergraduate Dental Students during Coronavirus Disease 2019 Pandemic in Nellore City: A Cross-sectional Study - Mounika Kamireddy; R. V. S. Krishna Kumar; Deepthi Athuluru; Srinivasulu Gomasani; V. Prathyusha Reddy; Punamalli Symon Prasanth (Wolters Kluwer Medknow Publications, 2024)
Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, education through online teaching became a new normal for India though it is fairly a very new concept for majority of students and teachers. As per the UNESCO estimates, COVID-19-related closure of educational institutions impacted the study of 1540 million students across 191 nations. Aim: The present study aimed to assess the effect of online teaching methods on dental education and perspectives among dental undergraduates. Materials and Methods: A cross-sectional study was conducted among 1st-, 2nd-, 3rd-, and 4th-year undergraduate dental students in Nellore city. A structured questionnaire was given through Google Forms regarding their opinion on comfort, flexibility, interaction, and stress during online teaching. It also included the impact of online teaching on academic performance and their preference for future curriculum. To assess the qualitative data, the Chi-square and Fisher's exact tests were applied. Statistical significance was set at P < 0.05. Results: Out of 266 who filled the questionnaire, 215 students never used online platform to attend classes before the pandemic. Eighty-nine percent were using smartphones to attend the classes. 38.3% are comfortable and 61.6% are not comfortable with online teaching. 74.4% of students responded that their preclinical and clinical learning was reduced since the transition to online teaching. There is no significant difference in content presentation, interaction, and response of lecturers. However, there is a lack of online quizzes or polls in between lectures. Conclusion: Overall, online teaching can be used as an adjunct rather than replacement for traditional classroom teaching in their future curriculum.